Fall Prevention: Reduce Your Risk! - Jennifer Hillan (EDIS)
Some lifestyle factors can affect your risk of falling. Find out how much you know about these factors by completing the crossword puzzle in this document. This document is FCS2231, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: April 2005.